2020
DOI: 10.1088/1755-1315/447/1/012047
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of land use and cover changes on ecosystem services value in urban highland areas

Abstract: Land use and cover (LUC) changes are one of the main factors in global environmental change. It directly affects the welfare of society through changes in environmental conditions, such as land degradation and ecosystem services value (ESV). These ecosystem services have a large impact on quality of life in urban areas in the highlands, such as the region of Takengon, and must be addressed in land use planning. The purpose of this study is to identify the impact of LUC on ESV in 2009 and 2014.Both LUC maps div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Agricultural and residential activities drive this lack of ecosystem services. These results are consistent with several other studies (de Groot et al, 2010;Estoque et al, 2018;Achmad et al, 2020. There are many changes in land cover. In this case, land-cover changes are due to community activities around the areas, in the form of illegal logging.…”
Section: Discussionsupporting
confidence: 93%
“…Agricultural and residential activities drive this lack of ecosystem services. These results are consistent with several other studies (de Groot et al, 2010;Estoque et al, 2018;Achmad et al, 2020. There are many changes in land cover. In this case, land-cover changes are due to community activities around the areas, in the form of illegal logging.…”
Section: Discussionsupporting
confidence: 93%
“…The LULC transformation uses the findings from previous research (Achmad et al 2023). The study location is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Decreases in ecosystem services brought on by LULC changes may have an effect on the region's actual and prospective resistance to factors brought on by human activity, as well as the livelihoods of those who depend on the land (Muche et al 2023). LULC changes have negative impacts on ecosystem services (Estoque and Murayama 2012;Achmad et al 2020). However, biodiversity resources that uphold the stability of ecological communities can enhance ecosystem functions (Li et al 2017).…”
Section: )mentioning
confidence: 99%
“…The tabulated data shows that the same LULC categories that experienced a decrease will continue to experience a reduction. In contrast, the same classes that experienced an increase will continue to experience an increase [45]. The categories that continue to experience a decrease in carbon stocks are forest, grassland, and bareland [1,2].…”
Section: Carbon Stock Changesmentioning
confidence: 98%